ChemInform Abstract: A Perovskite Electrocatalyst for Efficient Hydrogen Evolution Reaction. Issue 42 (September 2016) - Xu, Xiaomin; Chen, Yubo; Zhou, Wei; Zhu, Zhonghua; Su, Chao; Liu, Meilin; Shao, Zongping
Abstract: Polycrystalline A‐site Pr‐doped Prx (Ba0.5 Sr0.5 )0.5 Co0.8 Fe0.2 O3‐δ (x = 0—1) is prepared by reaction of the metal nitrates, EDTA, and citric acid in a 1(total metal ions):1:2 molar ratio (1.